2021
DOI: 10.1016/j.jsat.2021.108303
|View full text |Cite
|
Sign up to set email alerts
|

A real-world ten-week follow-up of the COVID outbreak in an outpatient drug clinic in Salamanca (Spain)

Abstract: Objective To compare over ten weeks the number of relapses, hospital admissions, calls made, admissions to therapeutic communities, face-to-face visits, treatment adjustment, number of injectables administered, and number of emergencies attended due to emotional and behavioral alterations and/or substance use disorder, and to describe and quantify social emergencies in an outpatient drug clinic (ODC) in Salamanca (Spain) from March 16, 2020, to May 22, 2020. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(17 citation statements)
references
References 36 publications
(31 reference statements)
0
17
0
Order By: Relevance
“…PPE [ 26 ] and masks [ 86 ] were also reported as being worn during interviews for two studies. Additional studies noted that facemasks were enforced during health check-ups [ 20 ] or in public [ 42 ], and encouraged while awaiting test results and in general patient areas of a health facility [ 51 ]. Rodriguez et al [ 12 ] described difficulties enforcing masks among PEH in shelters, with some giving up and only requiring them to be worn by staff.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…PPE [ 26 ] and masks [ 86 ] were also reported as being worn during interviews for two studies. Additional studies noted that facemasks were enforced during health check-ups [ 20 ] or in public [ 42 ], and encouraged while awaiting test results and in general patient areas of a health facility [ 51 ]. Rodriguez et al [ 12 ] described difficulties enforcing masks among PEH in shelters, with some giving up and only requiring them to be worn by staff.…”
Section: Resultsmentioning
confidence: 99%
“…Reluctance to follow and ambivalence regarding the importance of social distancing among PEH was noted in four studies [ 12 , 23 , 25 , 93 ]. Physical distancing was enforced among some PEH accessing homeless support services in the U.S. [ 97 ], during health check-ups in Salamanca [ 20 ], and during interviews for a study in Spain [ 26 ] and encouraged among patients accessing a psychiatric emergency room in Los Angeles [ 51 ] and shelter residents in Washington State [ 55 ]. One study in Ireland reported accommodation services were expanded to support social distancing [ 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations